iOS Applications Testing (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Mobile applications conquer the world, but iOS devices hold the major share of tablets market among the corporate workers. This study aims to identify the aspects (i.e. features and/ or limitations) that influence the testing of the native iOS applications. The aspects related to general mobile applications testing are identified through the systematic literature review of academic sources. iOS applications testing aspects are identified through the review of non-academic (multivocal) literature sources. The identified aspects are merged and discussed in detail using the reviewed sources and based on the author’s professional experience in iOS applications testing. The references to the credible sources are provided in order to support the professional experience findings. The study eliminates the gap that exists in the academic world in regards to iOS applications testing. The practitioners are also encouraged to fulfill their iOS applications testing strategies with the identified aspects.